2023
DOI: 10.1111/bcp.15659
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity and pharmacogenetics of doxorubicin in black Zimbabwean breast cancer patients

Abstract: AimsDoxorubicin‐induced cardiotoxicity (DIC) is a significant cause of mortality in cancer care. This study was conducted to establish the frequency of DIC in Zimbabwean breast cancer patients on doxorubicin and to test the DIC predictive power of genetic biomarkers.MethodsA cohort of 50 Zimbabwean breast cancer patients treated with doxorubicin were followed up for 12 months with serial echocardiography and genotyped for UGTA1A6*4, SLC28A3 and RARG. Eleven per cent of the patients experienced DIC.ResultsThe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…With respect to the genetic factors, the following are currently under investigation with potentially promising outcomes: polymorphisms in p53 (rs1042522) [ 313 , 314 ], NOS3 (rs1799983), NADPH oxidase (rs4673), GPX1 (rs1050450) [ 313 ], RARG [ 37 , 315 ], POLRMT [ 316 ] DPYD [ 317 ] and ABCC1 [ 318 ]. Interestingly, Varkoly et al, 2022 [ 319 ], demonstrated for the first time that circulating RNA virus gene sequences (e.g., influenza orthomyxovirus) were detected in the blood samples of patients with hematological malignancies or breast cancer and were associated with myocarditis and lower LVEF in response to chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the genetic factors, the following are currently under investigation with potentially promising outcomes: polymorphisms in p53 (rs1042522) [ 313 , 314 ], NOS3 (rs1799983), NADPH oxidase (rs4673), GPX1 (rs1050450) [ 313 ], RARG [ 37 , 315 ], POLRMT [ 316 ] DPYD [ 317 ] and ABCC1 [ 318 ]. Interestingly, Varkoly et al, 2022 [ 319 ], demonstrated for the first time that circulating RNA virus gene sequences (e.g., influenza orthomyxovirus) were detected in the blood samples of patients with hematological malignancies or breast cancer and were associated with myocarditis and lower LVEF in response to chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Future directions in PGx are also discussed with a focus on new clinical targets, methodologies and analysis approaches 3 . Bearing this in mind, Nyangwara et al provide insights on the prevalence of doxorubicin‐induced cardiotoxicity in black Zimbabwean breast cancer cohort and attempt to evaluate the predictive value of genetic biomarkers for cardiotoxicity 4 …”
Section: Figurementioning
confidence: 99%
“…3 Bearing this in mind, Nyangwara et al provide insights on the prevalence of doxorubicin-induced cardiotoxicity in black Zimbabwean breast cancer cohort and attempt to evaluate the predictive value of genetic biomarkers for cardiotoxicity. 4 Mechanistic insight into drug toxicity can be obtained also by using the data from metabolomic analysis to identify a drug candidate's off-targets; thus, metabolomics may also help to lay another pathway toward drug safety. Lim et al have identified glycine, hippuric acid sulfate, 3-hydroxydecanedioc acid and suberate as predictive biomarkers of predisposition to cisplatin-induced acute kidney injury (AKI) and speculated that metabolites indicative of mitochondrial dysfunction may serve as early markers of subclinical AKI.…”
mentioning
confidence: 99%